Hadith #2518 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; al-'Ala' bin 'Abdullah bin Rafa'i العلاء بن عبد الله بن رافع; Muslim bin Hatm مسلم بن حاتم (Sunan Abi Dawud)
‘Amr said “I heard from Abu Wa’il a tradition which surprised me, he then narrated the tradition to the same effect (as mentioned before).
Grade: Sahih